A autonomia da vontade do curatelado no exercício de atos da vida civil - Silva, Gilberto Antonio Neves Pereira da (2015)
This research consists in an investigative and theoretical work which aims to analyze the treatment given to an incapable person who is under curatorship protective measures as well as the limitations imposed by civil interdiction over his/her will’s autonomy. Curatorship is considered a relevant institute as long as it can lead to the whole suppression of one’s civil capacity when under curatorship, whose life is to be managed in all aspects by his/her curator, may it be in the financial, personal or public sphere. The Brazilian legislator apparently did not take some situations and peculiarities surrounding some specific cases into consideration, such as special needs in the daily person’s life, allowing the existence of remnants of a law both patrimonialist and individualist from last century over such matter. That demands the Judiciary intervention when enforcing curatorship rules, so that the will’s autonomy of the one under curatorship may not either unnecessarily or unfairly be suppressed. It must be enhanced that the 1988 Federal Constitution launch its effects over the Brazilian civil law, as for its coordinating role of private relations and the right to free development of the person’s will, showing the insight or comprehension as an inadequate criterion to assert one’s capacity, considering the present demands of the human being’s real life. In such a perspective, after a bibliographic review, limitations and isolation caused by curatorship over the life of the person declared incapacity have been realized, through a deductive methodology as well as the correlation of other keen subjects on the matter, and also by evaluating the implications caused both in the person and in the social ambience he/she lives. In face of the insight or comprehension criterion, it’s been observed that curatorship consequences may create limitations to the free development of personality, more precisely in the assertion of autonomous and independent affection and existential choices. It also restrains the person declared incapable to take part in contracts, leading to distortions, which include the patrimonial protection aimed by the codification and the obstacles imposed by the enforcement of fundamental rights constitutionally asserted, such as life, freedom and equality, not forgetting the rights to take part in public manifestations and assemblies.